Perforation of the Jejunum Secondary to AIDS-Related Gastrointestinal Kaposi's Sarcoma - Eric M Yoshida; Norman HL Chan; Clifford Chan-Yan; Robert M Baird (Canadian Journal of Gastroenterology)
Intestinal perforation in human immunodeficiency virus-positive patients due solely to Kaposi's sarcoma (KS) has rarely been described. A homosexual man with acquired immunodeficiency syndrome-related KS who presented with an acute abdomen is presented. He was found to have a jejunal perforation through a small KS lesion. There were no infectious organisms identified at the site of perforation.